Authorea
DOI: 10.22541/au.158446782.28121004
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality for Acute Pain in Outpatient Hysteroscopy: A Randomised Controlled Trial

Abstract: This a preprint and has not been peer reviewed. Data may be preliminary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(25 citation statements)
references
References 13 publications
0
25
0
Order By: Relevance
“…The original study of VRT in OPH by Deo et al 19 found a significant reduction in patient‐reported average pain, worst pain and anxiety scores by 28, 38 and 39%, respectively. with the use of VRT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The original study of VRT in OPH by Deo et al 19 found a significant reduction in patient‐reported average pain, worst pain and anxiety scores by 28, 38 and 39%, respectively. with the use of VRT.…”
Section: Discussionmentioning
confidence: 99%
“…A power calculation was performed to determine sample size based on data from a previous similar study investigating pain and anxiety with VRT use in OPH (figures for effect on anxiety were used for calculation, as there was a smaller difference than for pain scores between groups, VRT group mean 5.45, SD 3.35 and control group mean 3.30, SD 2.03) 19 . With a targeted 80% study power (β‐value) and 0.05 level of significance (α‐value), a minimum sample size of 38 participants in each group was estimated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have read with interest the study by Deo et al. published in BJOG: An International Journal of Obstetrics and Gynaecology 1 . We noted that although the control and the virtual reality (VR) group were ‘comparable’ regarding previous hysteroscopies, differences in baseline pain expectation scores between patients with a previous hysteroscopy and patients without previous hysteroscopy were not given.…”
mentioning
confidence: 99%
“…We would like to thank E. Mirza 1 and colleagues for their interest in our study, Virtual reality for acute pain in outpatient hysteroscopy: a randomised controlled trial 2 …”
mentioning
confidence: 99%